The invisible symphony - Chan, Cheong Jan; Jahnichen, Gisa (Universiti Putra Malaysia Press, 2013)
The continuous presence of the mass of insects in our living environment cannot be effectively seen with humans' limited view span, but could be heard clearly if we pay attention to the "audible world" that surround us. "Soundscape", simply the panoramic photograph of sound in an environment, offers another gateway to examine the ecological system. We are informed of the realities revealed through biophony(sound of the organisms), geophony(sound of the nature like wind streams) and anthrophony(man-made sounds including automobiles, machines as well as music)